Stomach cancer involving esophagus. Diagnosis, treatment and prevention by specific methods. - Filippov Yu. О.; Tyutyunnik, V. M. (Medicni Perspektivi, 2014)
Stomach cancer is a leader in the structure of cancer pathology in Ukraine and in the world. This paper summarizes own results and literature data on diagnosis, treatment and prevention of stomach cancer. Authors analyzed the experience and specific features of long-term treatment and diagnostic approach to patients with stomach cancer involving esophagus. Conducting pre-and postoperative cytostatic herbal therapy and cryosurgical operations during surgical treatment in patients with spread of tumor process allows to statistically significantly improve 3-and 5- year survival of patients.